The Metaphysical Club : [a story of ideas in America] - Menand, Louis (Farrar, Straus and Giroux, 2001)
Winner of the 2002 Pulitzer Prize for History. A riveting, original book about the creation of modern American thought. The Metaphysical Club was an informal group that met in Cambridge, Massachusetts, in 1872, to talk about ideas. Its members included Oliver Wendell Holmes, Jr., future associate justice of the United States Supreme Court; William James, the father of modern American psychology; and Charles Sanders Peirce, logician, scientist, and the founder of semiotics. The Club was probably in existence for about nine months. No records were kept. The one thing we know that came out of it was an idea -- an idea about ideas. This book is the story of that idea.